Does Immigration Affect the Natives' Mental Health? Causal Evidence from Forced Syrian Migration to Turkey - Mustafa Özer; Jan Fidrmuc (CESifo GmbH, 2024)
Large-scale immigration waves can have adverse effects on physical and mental health of the natives. We investigate the impact of the unprecedented influx of Syrian refugees after 2011 on the mental health of native Turks. Our results suggest that immigration may adversely affects the mental health of natives. The adverse effects, however, are conditioned by the underlying political environment: they are strong in opposition-controlled provinces but limited in areas controlled by the Justice and Development Party (AKP) of president Erdoğan. At the individual level, we observe adverse effects of immigration among married, older, less-educated, and employed women, for women with unemployed husbands, and for children with young or less-educated mothers or unemployed fathers. We believe these individual-level patterns reflect the combined effect of increased demand for health-care services and increased competition at the labor and marriage markets.
Keywords: F22; I12; J15; 330; health; mental health; immigration; instrumental variable; natural experiment